Synthesis, Characterization and Theoretical Studies of Novel Phosphonates as uPA Inhibitors - M. El-Nahas, Ahmed; M. Ali, Omar; M. Khalifa, Nagy; S. Ghazal, Basma (Current Organic Chemistry, 2014)
Synthesis and characterization of some novel phosphonate derivatives as uPA inhibitors have been conducted. HOMO and LUMO energies, NPA charges, electrophilicity index and vibrational frequencies were calculated for the current and previously reported phosphonates. Based on the calculated properties, the results obtained indicate that the novel compounds are expected to be more potent than other phosphonates.
Keywords: SAR